2013
DOI: 10.1177/0885066613516594
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Death and Prolonged Renal Insufficiency in Ethylene Glycol Poisoning

Abstract: Background: We assessed the predictive value of selected factors on the outcomes of death and prolonged renal insufficiency (RI) from ethylene glycol poisoning. Methods: Retrospective, observational California Poison Control System study, over a 10-year period (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). We compared 2 groups. The first group (D/RI) included 59 patients who died (9 patients) or had prolonged RI (50 patients). Prolonged RI was defined as kidney injury in which dialysis was requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Administration of antidote >6 h after arrival at the hospital has been associated with death and renal failure. 16 In this case, early diagnosis and recognition, and collaboration with the laboratory, pharmaceutical department, pharmaceutical company, and the police led to rapid intervention with fomepizole after the initial treatment with 10% ethanol infusion. The exact onset time was unknown, and it was unclear whether the treatment should be started within 6 hours; nonetheless, it was started immediately.…”
Section: Discussionmentioning
confidence: 95%
“…Administration of antidote >6 h after arrival at the hospital has been associated with death and renal failure. 16 In this case, early diagnosis and recognition, and collaboration with the laboratory, pharmaceutical department, pharmaceutical company, and the police led to rapid intervention with fomepizole after the initial treatment with 10% ethanol infusion. The exact onset time was unknown, and it was unclear whether the treatment should be started within 6 hours; nonetheless, it was started immediately.…”
Section: Discussionmentioning
confidence: 95%
“…Alcohols such as methanol and ethylene glycol may rarely present with seizure [6,7]. However, our patient has no clinical history of access to these alcohols, had no evidence of an osmolal gap, and has not developed worsening severe acidosis.…”
Section: Case Continuedmentioning
confidence: 76%
“…In a retrospective study, Lung et al observed that patients presenting with comatose or seizures were those who had renal insufficiency. When compared with survivors who recovered without complications, they initially had a lower mean arterial pH (7.03 vs 7.27) and higher initial serum creatinine (1.7 vs 1.1) 13. According to Coulter et al, higher OG and anion gap have also been associated with higher risk of death 14…”
Section: Discussionmentioning
confidence: 99%